About imagination and fantasy: considerations about the ornament (Revista Música, 2016)
The objects of this study are the conditions of Imagination and Fantasy as principles of representation in arts between the Mannerism and Rococo. The analysis was focused in the ornamentation by floral inspiration. In this case the seminal condition of the Fantasy was historically joined to the concept of development and variation. Studied as a “Corpus” with structural self-sufficiency, the ornament between centuries XVI and XVIII has derived in a rigorous way from organization forms and its commanded distinct languages to them. Was observed the development of a conducted taste for affinities with the variations of the curve and also the advent of the transition of the ornament while structure condition.